FAKTOR RISIKO TERJADINYA SEROTINUS DI RSUD KRATON PEKALONGAN TAHUN 2009 - Rosi Kurnia Sugiharti; Fitrah Fulanan (Viva Medika, 2010)
Background : The maternal mortality rate in Pekalongan likely to decline fromyear to year, but in 2009 there was an increase to 157.58 / 100,000 live births.The causes of maternal death include severe pre eclampsia as much as 2 cases, 1case of bleeding, heart failure 1 case, and 1 case embolism. In the case of thebleeding can be caused by high-risk pregnancies including serotinus. Based onthe results of pre-survey on January 1, 2010, found the incidence of RSUD KratonPekalongan serotinus in the period from January 1 to December 31, 2009 asmany as 67 cases. Genesis serotinus not be separated from the various factorsthat influence it.Objective : The purpose of this study was to identify risk factors for serotinuspicture in RSUD Kraton Pekalongan period of 2009.Method : The research design was a descriptive quantitative approachrestropective. The sample in this study is the birth mother with serotinus in RSUDKraton Pekalongan period 1 January to 31 December 2009. The type of data usedin this research is secondary data. The variable in this study is a single variablethat is a risk factor for serotinus.Result : The research design was a descriptive quantitative approachrestropective. The sample in this study is the birth mother with serotinus in RSUDKraton Pekalongan period 1 January to 31 December 2009. The type of data usedin this research is secondary data. The variable in this study is a single variablethat is a risk factor for serotinus.Conclusion : A risk factor for serotinus in RSUD Kraton Pekalongan in 2011 onthe factors oligohydramnion found as many as 61.20%, a factor in the history ofthe family was found as much as 49.25%, a factor previously found serotinushistory as much as 34.33%, mostly in the age range 20-35 year (91.04%), andmost were multiparous (62.69%). Keyword : The risk factors affecting serotinus